Key aspects about education for refugee children - Vega Pascual, Mª Jesús (Revista Española de Educación Comparada, 2003)
This presentation entitled «Key Aspects about Education for Refugee Children:Refugee Camp Situation», is based on the 2003 UNHCR Guidelines on Education and highlights the relevance of the education even in situations of emergency and crisis, interms of protection and psychosocial well-being of children. It also mentions key issues to consider when working with refugees, internally displaced people, asylum-seekers,stateless and other populations of concen to UNHCR. Aspects such as refugee children’s rights, UNHCR policy commitments to education, participation of refugees and their communities in the design, establishement and implementation of education programmes, specially in emergencies, will be dealt with in this presentation. It will alsomentions topics such as the school drop out, education for vulnerable groups and the need for promoting a gender sentitive approach, bearing in mind that the hard experience of exile, the changes of family structure, the ethnic, cultural, religious and legal differences are key when working with this population Esta presentación titulada "Consideraciones esenciales sobre la educación de los niños refugiados: la situación en los campos de refugiados", está basada en las Directrices del ACNUR sobre Eduación de 2003, y pretende resaltar la importancia de la educación en las situaciones de refugiados, incluso en situaciones de emergencia o crisis, y cómo ésta juega en favor de la protección y del bienestar psicosocial de los niños. Se mencionan las peculiaridades más relevantes que deben tenerse en cuenta cuando se trabaja con refugiados, desplazados internos, solicitantes de asilo, apátridas y otras poblaciones de las que se ocupa el ACNUR. Se verán aspectos como los derechos de los niños refugiados, los compromisos del Alto Comisionado en materia de Educación, la participación de los refugiados y sus comunidades para diseñar, establecer e impartir programas de educación especialmente necesarios en situaciones de emergencia. También se abordarán los factores que influyen en el absentismo escolar en los campos de refugiados, el apoyo a los grupos más vulnerables y la importancia de tener siempre presente un enfoque de género en este ámbito, sabiendo que la dura experiencia del exilio, la re-estructuración de la unidades familiares, así como las diferencias étnicas, culturales, religiosas, legales y de otra índole, juegan un papel especialmente relevante en el trabajo con este colectivo